Cell polarity (the 'four lines') distinguishes gastric dysplasia from epithelial changes in reactive gastropathy. Issue 3 (14th October 2020) - Waters, Kevin M; Salimian, Kevan J; Assarzadegan, Naziheh; Hutchings, Danielle; Makhoul, Elias P; Windon, Annika L; Wong, Mary T; Voltaggio, Lysandra; Montgomery, Elizabeth A
Abstract : Aims: Gastric dysplasia is a risk factor for synchronous and subsequent gastric carcinoma. Distinguishing gastric dysplasia from reactive changes is subject to interobserver disagreement and is a frequent reason for expert consultation. We previously used assessment of surface cell polarity (the 'four lines') as a key feature to decrease equivocal diagnoses in Barrett oesophagus. In the current study, we examined for the presence or absence of the four lines in gastric dysplasia and reactive gastropathy. Materials and methods: The study includes all ( n = 91) in‐house biopsies with at least gastric dysplasia from the surgical pathology archives of two academic institutions during a 5‐year period from 2008 to 2012. A reactive gastropathy group ( n = 60) was created for comparison. Results: The dysplasia/neoplasia group was comprised of 14 biopsies of gastric foveolar‐type dysplasia, 59 of intestinal‐type dysplasia, 14 with dysplasia in fundic gland polyps, three pyloric gland adenomas and one oxyntic gland adenoma. Loss of surface cell polarity was seen in all 88 dysplasia cases with evaluable surface epithelium. All 57 reactive gastropathy cases with evaluable surface epithelium showed intact surface cell polarity except in focal areas directly adjacent to erosions in 17 cases, where the thin wisp of residual surface mucin could not be appreciated on haematoxylin and eosin. Conclusion: Surface cell polarity (the four lines) was lost in all gastric dysplasia biopsies with evaluable surface epithelium and maintained in all biopsies of reactive gastropathy. Caution should be taken in using this feature adjacent to erosions in reactive gastropathy.